Growth Horizons for a Changing Asian Regional Economy - David Roland-Holst; Guntur Sugiyarto (Asian Development Bank (ADB), 2014)
After two generations of economic growth, the next phase of structural transformation for Asia will have several salient features. Our results suggest that no single policy orientation, pathway, or even destination will apply to all economies. The main driver for each economy's structural change will be demand, both domestic and external. These demand sources can have very different sector emphasis, however, and drive domestic resource allocation in different directions. Asian economies with high export shares will be drawn to more intensive primary and industrial resource allocation, while those with larger domestic demand shares will become more service-oriented. Our long-term forecasts for the Asian economies suggest that factor productivity growth continues to be essential to improving livelihoods generally and promoting regional convergence in particular. Of particular importance is potential for reducing regional inequality through more inclusive growth - productivity improvements are more cost-effective in lower-income countries and they have a bigger relative income dividend. Our research also reveals that services are essential contributors to average living standards in high-, medium-, and even low-income Asian economies. For this reason, policies that improve the efficiency of service sector labor allocation, as well as skill and productivity improvements via determined education and training programs, will be essential to sustaining higher living standards and transition to long-term growth sustained by demand from an ever-expanding middle class.
hdl:11540/1977
Keywords: C51; C53; E37; F17; F18; O47; 330; structural transformation; factor productivity; Asian financial integration; service sector